The Impact of Corporate Social Responsibility Programs on Sustainable Development: An Applied Study in National and Foreign Companies Operating within Petrochemical Industries in the Kingdom of Saudi Arabia - Al-Qahtani, Ayed bin Ali (The Arab Journal of Administration, 2025)
The current study aimed to identify the extent of the impact of Corporate Social Responsibility programs on achieving sustainable development in the petrochemical industries sector in the Kingdom of Saudi Arabia, and the study focused on three main axes: corporate social responsibility, sustainable development, and the relationship between them, using a descriptive analytical approach. The study community was represented by managers and their assistants working in departments related to the practice of Social Responsibility programs in (5) companies in the petrochemical industries sector in the Kingdom of Saudi Arabia included in the list of the Saudi Capital Market Authority (Tadawul) for the year 2023, which is among the list of the 100 largest companies in the petrochemical industries sector worldwide in terms of market capitalization. The results of the study showed the interest and orientation of companies towards the implementation of Corporate Social Responsibility programs, and the results also showed a significant impact of the economic dimension of social responsibility on achieving the social and environmental dimension of sustainable development in the Kingdom of Saudi Arabia. In addition, there is a significant moral impact of the charitable dimension of social responsibility on achieving the social and environmental dimension of sustainable development in the Kingdom of Saudi Arabia, which indicates that the implementation of CSR programs can positively contribute to achieving sustainable development of the social and environmental dimension.